PERANCANGAN MEDIA EDUKASI PUBLIK TENTANG FUNGSI DAN LAYANAN PERUM BULOG KANTOR WILAYAH BALI SEBAGAI PERUSAHAAN LOGISTIK PANGAN - Permatahati, Ayu Leony Mahadewi Putri; Swandi, I Wayan; Udayana, Anak Agung Gde Bagus (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2025)
Public education media plays an important role in conveying information to the public effectively, especially regarding government agency and company services that have a direct impact on public welfare. Perum Bulog Kanwil Bali as a food logistics company has a strategic function in maintaining the availability and stability of food prices in the Bali region. However, the lack of public understanding of Bulog's role and services creates a need for educational media that can convey information clearly and attractively. This study aims to design public education media that educates the public about the functions and services of Perum Bulog Kanwil Bali, especially in the management of food logistics such as procurement, distribution, and storage of staple foods. The methods used in designing this media include analyzing the information needs of the community, reviewing literature, and applying the principles of visual communication design. The resulting media include infographics, animated videos, and digital campaigns that can be accessed through various platforms.